SELF-DEVELOPMENT FOR CADEMIC SUPPORT STAFF OF SILPAKORK UNIVERSITTY. - Srathonghom, Parichat (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The purpose of this research are 1) Study the level self-development for academic support staff of Silpakorn University. 2) Compare the level self-development for academic support staff of Silpakorn University by classified accoiding to personal factors. 3) Study guidclines self-development for academic support staff of Silparkorn University. The sample group of 518 academic supporting staffs from Silpakorn University by stratified random sampling and 5 interviewes were selected by purposive sampling. The research intrument are questionnaire and interview. Statistic in this research used the frequency, percentage, average valve , standard deviation (S.D.) , t-test, one-way ANOVA and content analysis. 1. Self-development for most academic support staff of silplkorn University want the agency to promote continved education in order to enhance performance. Training seminar study is cncovraging personnel to develop their skills continuously. Mastering yourself is train yourse If to always timely. Personality development isn’t drinking beer and addictive substance intoxication. Access to agencies that want to encourage advancement opportunities by encovraging the study or to train them. 2. The academic support staff with sex. Status, education level and the average income per month are different. The overall opinion are no different. But theage, faculty/agenciecs, job responsibilities period of performance. There anre different opinions on the self-derelopment. The overall difference is statistically significant at the .05 level. 3. Supporting Self-development for academic supporting staffs. Should scholarship support more and enough with the actual expenses abroad. Support education in the field of people interest and want to go study abroad. Added motivation when graduation. The training focused on topics that personel are interested, have recreation activity for training to reduce boredom in the training. Supply of new books, access the library all the time and plan activities to focus staff favorite in the librarg. Invite practicing meditation before working. Meeting the personel to clarify the understandin the opportunity to contribute to the request of the personel. Article history : Accepted 18 April 2017 SIMILARITY INDEX = 0.00